The multi‐BRCT domain protein DDRM2 promotes the recruitment of RAD51 to DNA damage sites to facilitate homologous recombination. Issue 3 (4th March 2023) - Yu, Chen; Hou, Longhui; Huang, Yongchi; Cui, Xiaoyu; Xu, Shijun; Wang, Lili; Yan, Shunping
Summary: DNA double‐strand breaks (DSBs) are the most toxic form of DNA damage in cells. Homologous recombination (HR) is an error‐free repair mechanism for DSBs as well as a basis for gene targeting using genome‐editing techniques. Despite the importance of HR, the HR mechanism in plants is poorly understood. Through genetic screens for DNA damage response mutants (DDRMs), we find that the Arabidopsis ddrm2 mutant is hypersensitive to DSB‐inducing reagents. DDRM2 encodes a protein with four BRCA1 C‐terminal (BRCT) domains and is highly conserved in plants including bryophytes, the earliest land plant lineage. The plant‐specific transcription factor SOG1 binds to the promoter of DDRM2 and activates its expression. In consistence, the expression of DDRM2 is induced by DSBs in a SOG1‐dependent manner. In support, genetic analysis suggests that DDRM2 functions downstream of SOG1. Similar to the sog1 mutant, the ddrm2 mutant shows dramatically reduced HR efficiency. Mechanistically, DDRM2 interacts with the core HR protein RAD51 and is required for the recruitment of RAD51 to DSB sites. Our study reveals that SOG1‐DDRM2‐RAD51 is a novel module for HR, providing a potential target for improving the efficiency of gene targeting.